DEVELOPMENT AND VALIDATION OF AN ANALYTICAL METHODOLOGY FOR COCAINE HYDROCHLORIDE DETERMINATION IN A SYNTHETIC POLYMER BY ULTRAVIOLET SPECTROMETRY - BONILLA Q., Dorelly A.; PEÑUELA B., Luisa F.; SIERRA M., Noralba; DÍAZ F., Josías E.; ROJAS B., Jaime H. (Vitae, 2009)
An ultraviolet spectrometry method was developed for the quantitative assay of cocaine hydrochloride in a latex plastic polymer. The absorption was determined in sulfuric acid 0,5N at 233 nm, after substance extraction using the same acid. Selectivity, linearity between 4 and 20 ppm and good reproducibility were shown by this method. Detection and quantification limits were 1,6 and 4,0 ppm, respectively. Method robustness was also verified, as well as cocaine hydrochloride stability in sulfuric acid 0,5N, medium where the samples and reference standards were stored. These properties, besides its simplicity and accuracy, make it suitable for achieving proposed objectives. The validated method was applied to the determination of cocaine hydrochloride in polymer confiscated by the law